Does Fluency Mean Intelligibility? A Mixed Methods Study on the Perceptions of Speech Fluency and Its Teaching among L2 English Teachers in Finland - Ollila, Matti (My University, 2024)
This thesis examined how the concept of speech fluency is perceived by 85 L2 English teachers in Finland, in addition to finding out how they teach it in their classrooms. The study was a partial replication of an earlier study by Tavakoli and Hunter (2018). The general aim of the study was to investigate how the speech fluency research findings have been implemented into the classroom and how knowledgeable the teachers are about them. The data for the study were collected through a questionnaire that was a preliminary assignment for an in-service teacher training module on speech fluency that the participants voluntarily decided to attend. The in-service teacher training module was organized in the School of Languages and Translation Studies at the University of Turku during 2022–2023 (funded by the Finnish National Agency for Education), and the questionnaire data were collected as part of the Fluency and Disfluency Features in L2 Speech project (funded by the Research Council of Finland in 2020–2024). The questionnaire included 15 statements answered on a four-point Likert-scale, in addition to qualitative short answer and open-ended descriptive questions, out of which two were included in this thesis, while three were excluded. The self-reported quantitative data showed that, in general, the teachers were fairly confident in their knowledge of speech fluency, its aspects and how it’s taught. However, when it comes to the qualitative answers and the tasks of defining a fluent speaker and listing activities that they would use to promote fluency, the participants rarely restricted their descriptions to the narrow sense of the concept, often using elements that better describe general speaking ability. When it comes to their studies or other training, the teachers of the study did not feel very educated about speech fluency or the latest research findings regarding it. However, many of the teachers thought that these research findings could help them promote speech fluency in the classroom. The findings of this study can benefit every actor of the education system by being more knowledgeable about speech fluency and making them work towards a unified way to define, teach, assess, and specify speech fluency across the board.
Keywords: speech fluency, language teaching, defining fluency, promoting fluency, classroom practice, teacher understanding